Espacio urbano y la modernización del alumbrado público en la ciudad de Puebla entre 1888 y 1910 - Edna Hernández (Les Cahiers ALHIM)
The adoption of the electric lighting in the city of Puebla during the Porfiriato, was much more than the modernization of a service. For the society of Puebla at the end of the nineteenth century and the beginning of the twentieth century, the introduction of electric light means form part of modern cities, since it took one of the Technological advances of the era. The lighting of the urban space in this historical period was carried out chiefly by the town hall, however the multiple failures of the new service impetus to certain individuals, especially businessman to illuminate by themselves their business. All of this quickly transformed the urban physiognomy at the same time that generated new practices of the city nightlife. This article explores the first decades of electric lighting in the city and the transformations that it implied transformations not only physical otherwise also social changes as the arrival of new services such as restaurants, cafe and cinemas and new festive activities that led to an intensification of the practice and the appropriation of urban space during the night and a new perception what meant the nightlife.